2016
DOI: 10.1111/mec.13571
|View full text |Cite
|
Sign up to set email alerts
|

The hitchhiker's guide to Europe: the infection dynamics of an ongoingWolbachiainvasion and mitochondrial selective sweep inRhagoletis cerasi

Abstract: Wolbachia is a maternally inherited and ubiquitous endosymbiont of insects. It can hijack host reproduction by manipulations such as cytoplasmic incompatibility (CI) to enhance vertical transmission. Horizontal transmission of Wolbachia can also result in the colonization of new mitochondrial lineages. In this study, we present a 15‐year‐long survey of Wolbachia in the cherry fruit fly Rhagoletis cerasi across Europe and the spatiotemporal distribution of two prevalent strains, wCer1 and wCer2, and associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
118
4
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(134 citation statements)
references
References 66 publications
(179 reference statements)
8
118
4
4
Order By: Relevance
“…The incongruence of the Wolbachia phylogeny with that of its hosts suggests that haplodiploid scolytine beetles have acquired different Wolbachia strains horizontally from independent sources. Previous studies have shown that the ecological overlap of different species by sharing the same host provides the opportunity for Wolbachia exchange between different species (Stahlhut et al, 2010;Schuler et al, 2013;2016). Different factors, such as shared parasitoids (Heath et al, 1999;Vavre et al, 1999;Ahmed et al, 2015), cannibalism (Le Clec'h et al, 2013) and the host plant itself (Sintupachee et al, 2006), can facilitate the switch between different species boundaries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incongruence of the Wolbachia phylogeny with that of its hosts suggests that haplodiploid scolytine beetles have acquired different Wolbachia strains horizontally from independent sources. Previous studies have shown that the ecological overlap of different species by sharing the same host provides the opportunity for Wolbachia exchange between different species (Stahlhut et al, 2010;Schuler et al, 2013;2016). Different factors, such as shared parasitoids (Heath et al, 1999;Vavre et al, 1999;Ahmed et al, 2015), cannibalism (Le Clec'h et al, 2013) and the host plant itself (Sintupachee et al, 2006), can facilitate the switch between different species boundaries.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, incongruence between the phylogeny of Wolbachia and its host shows that these bacteria can switch species boundaries and move horizontally between species Watanabe et al, 2012). The close ecological relationship between different species, such as shared habitats or shared parasitoids, can facilitate the horizontal transmission of Wolbachia (Heath et al, 1999;Stahlhut et al, 2010;Schuler et al, 2013;2016;Ahmed et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In insects, this is often found in the context of an infection with the endosymbiont Wolbachia that can manipulate its hosts reproduction (through e.g., mate-discrimination, cytoplasmic incompatibilities;Hoffmann, Turelli, & Simmons, 1986;Schuler et al, 2016). femoratus PS and Ca.…”
mentioning
confidence: 99%
“…Finally, it is also possible that endosymbionts could restrict gene flow between the Prunus and Lonicera host races. If the endosymbiont, Wolbachia, infects Prunus flies at higher levels than it does Lonicera flies, which appears to be the case (Schuler et al, ), it will establish a form of unidirectional incompatibility between infected Prunus males and uninfected Lonicera females, strengthening RI between the host races (Telschow, Flor, Kobayashi, Hammerstein, & Werren, ). As such, unidirectional CI can also help account for the pattern of geographic and host‐associated genomic differentiation in R. cerasi , as based on our current knowledge of the system, unidirectional CI is expected to reduce gene flow but not stop it entirely (Boller & Bush, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the timing of endosymbiont acquisition differs between Prunus and Lonicera flies. Wolbachia , a maternally inherited endosymbiont, which causes unidirectional incompatibilities between infected males and uninfected females of R. cerasi , reached fixation in Prunus flies, while only infecting 17% of Lonicera flies in German populations (Schuler et al, ). These results provide some evidence of phenotypic differentiation among host‐associated flies and suggest that mating may not be entirely random.…”
Section: Introductionmentioning
confidence: 99%